Pengaruh Guncangan Pertumbuhan Ekonomi Negara Mitra Dagang Utama Indonesia Terhadap Dinamika Makro Ekonomi Indonesia - Rizky Wahyudi; Selli Nelonda (Universitas Negeri Padang, 2025)
This study aims to analyze the impact of external shocks on the dynamics of Indonesia's macroeconomy, transmitted through its main trading partners China, Japan, and the United States, using the Structural Vector Autoregression (SVAR) method. Stationarity testing with the Augmented Dickey-Fuller (ADF) test confirms that all variables are stationary at level. The optimal lag selection identifies lag 1 as providing the most stable model. The results show that Indonesia’s macroeconomic variables—trade balance, per capita investment, per capita consumption, and per capita economic growth—respond to external shocks in a fluctuating manner but tend to return to equilibrium in the long run. GDP shocks from China positively affect investment, consumption, and economic growth, although they worsen the trade balance due to increased imports. Shocks from Japan have a more limited positive effect, while shocks from the United States tend to have negative impacts through global financial channels. These findings highlight the importance of diversifying trade partners and strengthening the domestic economic structure. Furthermore, investment plays a critical role in driving long-term economic growth by creating jobs, enhancing efficiency, and increasing competitiveness. Therefore, maintaining a conducive investment climate and strengthening international trade are essential to improving Indonesia’s economic resilience and performance amid global economic dynamics.